Climate Risk Country Profile : Kazakhstan - World Bank Group; Asian Development Bank (World Bank, Washington, DC and Asian Development Bank, Manila, 2021)
The Republic of Kazakhstan is located in Central Asia, the country shares borders with the Russian Federation to the north, China to the east, and Turkmenistan, Uzbekistan, and the Kyrgyz Republic to the south. The Caspian Sea forms a natural boundary to the west. Kazakhstan contains forest-steppe, steppe, semi-arid, and desert climate zones and precipitation is low throughout. This document aims to succinctly summarize the climate risks faced by Kazakhstan. This includes rapid onset and long- term changes in key climate parameters, as well as impacts of these changes on communities, livelihoods, and economies, many of which are already underway. This is a high-level synthesis of existing research and analyses, focusing on the geographic domain of Kazakhstan, therefore potentially excluding some international influences and localized impacts. The core data presented is sourced from the database sitting behind the World Bank Group’s (WBG) climate change knowledge portal (CCKP), incorporating climate projections from the Coupled Model Inter-comparison Project Phase 5 (CMIP5). This document is primarily meant for WBG and Asian Development Bank (ADB) staff to inform their climate actions. The document also aims and to direct the reader to many useful sources of secondary data and research.